Effects of canine movement on maxillary anterior en-masse retraction with clear aligners: a finite element study - Xin Yue Tang; Ting Jiang; Han Su; Daphne Yuchen Chin; Jia Yi Chen; Yu Qi Qin; Guo Hua Tang (BMC Oral Health)
Abstract Background In clear aligner therapy, tooth movement can be designed individually by computer software. However, the deformation of the aligner created by the virtual movement of one tooth may affect the actual movement of other teeth. This study aimed to evaluate the impact of the amount of canine movement on the responses of incisors and posterior teeth during maxillary anterior en-masse retraction with clear aligner. Methods A three-dimensional finite element model of maxillary dentition was constructed for first premolar extraction. The incisors were retracted by 0.15 mm with an intrusion of 0.10 mm. The canine was bodily retracted in six groups with different amount of 0 mm, 0.10 mm, 0.15 mm, 0.20 mm, 0.25 mm, and 0.30 mm. The groups were named after the amount of canine movement. Separate canine retraction of 0.25 mm was set in an additional group. ANSYS® software was used to calculate the initial displacements and forces on the dentition in each group. Results In incisor retraction with no canine movement (group 0), the incisors underwent uncontrolled lingual tipping and the canine exhibited mesial tipping. As the amount of canine movement increased, the lingual retraction force and clockwise moment on the incisors gradually weakened. The incisors exhibited less lingual inclination with more extrusion, while the canine displayed more distal inclination and less extrusion. The central and lateral incisors showed controlled lingual tipping and lingual root movement respectively in group 0.25, and both the incisors inclined labially in group 0.30. During separate canine retraction, the canine experienced distal tipping and the incisors showed labial tipping. Posterior teeth exhibited mesial tipping in all groups, the amount of which was in positive correlation with the amount of canine movement. Conclusion During en-masse retraction with clear aligner, the uncontrolled lingual tipping of incisors can be eliminated by increasing the amount of canine retraction. Practitioners need to pay attention to the reciprocal effects of the designed tooth movements during clear aligner therapy.